(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Base isolation is one of the most promising alternatives among the structure control methods. In recent decades, base isolation has been seriously considered for civil structures, such as buildings and bridges, subjected to ground motion. Seismic isolation technique had been applied successfully abroad, especially in Japan, and buildings with seismic isolation design had good performances in the earthquakes before. Seismic isolation technique has developed well in recent years in our country. After the Wenchuan earthquake, some departments revised the Code for Seismic Design of Buildings and relaxed some restraint of seismic isolation design. Using the isolation design correctly the buildings can get a good capability of seismic resistance. It is a good choice for the reconstruction of the important buildings. Focus on description of the concept of seismic design and the design method of base-isolated structure of Zundao CentralSchooland hospital.